2021
DOI: 10.21203/rs.3.rs-604692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health System Strengthening Using Problem Solving for Better Health in Lesotho

Abstract: Background Problem Solving for Better Health ® (PSBH ® ) is a system-strengthening workshop designed to empower healthcare workers (HCWs) to solve problems. We report on the perspectives of HCWs trained in PSBH to better understand the impact and challenges of PSBH in Lesotho, a country with among the highest prevalence of HIV and tuberculosis in the world.Methods HCWs who attended PSBH workshops in 2018 – 2019 were interviewed using a semi-structured interview guide developed from a hybrid conceptual framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, yeasts and total coliforms positively correlate with molds and thermotolerant coliforms. Total coliforms and thermotolerant coliforms in food indicate fecal contamination [24]. Tis study found total and thermotolerant coliforms in fermented porridges, which suggests potential contamination by pathogenic E. coli.…”
Section: Discussionmentioning
confidence: 68%
“…However, yeasts and total coliforms positively correlate with molds and thermotolerant coliforms. Total coliforms and thermotolerant coliforms in food indicate fecal contamination [24]. Tis study found total and thermotolerant coliforms in fermented porridges, which suggests potential contamination by pathogenic E. coli.…”
Section: Discussionmentioning
confidence: 68%